Pengaruh Faktor Eksternal Terhadap Strategi Pemasaran Pada Mcdonald’s - Adi Neka Fatyandri; Febbryan Zhangrinto; Hendro Hendro; Katherine Katherine; Nancy Nancy; Steven Steven (Public Service and Governance Journal, 2023)
Consumer interest in McDonald's, which is operated as a franchise, remains high in Indonesia and elsewhere. McDonald's is one of the franchises that has expanded the most both in Indonesia and internationally. The term "strategy" is used to describe the ways through which a corporation works to fulfill its purpose and vision over a certain period of time. Analyzing the company's external elements is essential before developing a marketing plan. The organization has to analyze its external environment in order to recognize threats and seize opportunities. The goal of this study is to determine whether external influences have an impact on McDonald's business strategy. The research approach used here is a case study based on a SWOT analysis. This information is derived from other sources. Meanwhile, qualitative research is being undertaken. Many data sources are used in this method to investigate a topic from several angles. Materials like magazines, newspapers, periodicals, and articles. In a situation when the firm's strengths are 1.45 and its shortcomings are 0.50, the company is doing really well. In light of the 2.12 opportunities and 1.8 risks present. The study's findings suggest that the fast food restaurant in question has sound management practices and can compete well in an industry where many similar enterprises can be found.